Penatalaksanaan Fisioterapi Pada Efusi Pleura Di RS Paru Dr. Ario Wirawan Salatiga - Permana, Irham Akbar Nugraha, Isnaini Herawati S.St. Ft, M.Sc (2016)
Background :pleural effusion is a medical condition where the liquid in the lung is increased and pilled up in the pleural cavity. It makes a limitation of pleural ability to inflate and deflate, so that people feels difficult to breathe. In this case, we need a physiotherapy intervention to face the problems occurs from pleural effusion by implementing infrared and diaphraghmatic breathing exercise. Objective :To know what the benefits of theimplementation of physiotherapy by using infrared anddiapraghmatic breathing exercise to the pleural effusion to relieve the shortness of breath, chest pain, and improve the thorax mobility. Result and Findings :A decrease in the degree of chest pain when coughing before doing treatment (T0) 6,9 cm (moderate pain) and after doing the treatment in six times (T6) becomes 1,5 cm (a little bit pain). An increase in thoracic cage expansion in axilla from T0 = 3 cm, the difference becomes T6 = 3 cm, in intercostallis area IV from T0 = 2 cm, the difference belongs to T6 = 3 cm, and in procecus xyphoideus area from T0 = 2 cm, the difference belongs to T6 = 3 cm. There is a decrease in the degree of shortness of breath T1 = 5 cm (severe shortness) to T6 = 2 cm(slight shortness). Conclusion :The writer can conclude that there is a successfulness in decreasing the number of shortness of breath, chest pain, so a increase of thorax mobility in the case of pleural effusion.